Indicators of Effective Social Care Interventions Administered to Looked-After Youths and Children - Amos Magut; Rose Otieno; Godfery Ng'eno (Asian Social Work Journal, 2020)
This study is based on a review of literature on social interventions given to children and the youth in institutional contexts. From the review, the study reports that the efficacy of social interventions may be ascertained by the presence of the following indicators in looked-after children: attachment to caregivers and peers, social connectedness, interpersonal competence, sense of autonomy. Based on these results, the study recommends that institutions of care need to develop a framework for evaluating their social programmes that integrate these indicators. Such an evaluation programme would offer a comprehensive framework for enhancing programme efficiency and continuous improvements of the standards of care given to looked-after youths and children. Despite being based on a review of literature, this study make important suggestions on the most effective ways for helping looked-after youths to cope with life’s difficulties now and in the future. The paper may help care homes to provide an environment conducive for social restoration and nurturing of healthy youths and children. This forms an important foundation to the holistic development of youths and their ability to achieve success in school, work, and social interactions. The study also provides useful information to the government, scholars and other child-care stakeholders on the actual effect of the social interventions on development of resilience factors like optimism, active coping, hardiness and purpose in life.